Analisis Kemampuan Argumentasi Ilmiah Siswa Dengan Penggunaan Media Photovoice Pada Materi Pembiasan Cahaya (Universitas Negeri Surabaya, 2022)
Abstract The challenge of education in Indonesia in the 21st century is that at least students need to have critical thinking competencies and effective communication, students can practice these competencies by having good scientific argumentation skills. Arguments are easier when using media such as photovoice, with photovoice helping students express something that is being discussed. This study focuses on and aims to determine the level of scientific argumentation ability of students using Photovoice media on light refraction material in class XI IPA SMAN 1 Sumberrejo. The method used is mixed quantitatively and qualitatively, with quasi-experimental. The population in this study were all students of class XI IPA SMAN 1 Sumberrejo as many as 210 students, with a sample of 30 students in class XI IPA 6 of SMAN 1 Sumberrejo. Students' scientific arguments were measured using an essay test with photovoice media. Quantitative data analysis used a one-sample t-test, while qualitative data analysis used the TAP (Toulmin's Argumentation Pattern) pattern component. Based on the results of calculations using the one-sample t-test, which was carried out twice, it showed that the students' scientific argumentation ability scores were in a good category. The results of coding students' scientific argumentation patterns using TAP obtained an average score of 2.34 this score was in a good category, as well as stated in the percentage of 77.4% of students got a good category. Based on the results of the analysis, it can be concluded that the value of the scientific argumentation ability of students using photovoice media on light refraction material is in a good category, although it is difficult to develop arguments both written and oral because it is based on students who do not understand the concept of the material well. Keywords: Student's scientific argumentation, photovoice, Toulmin's argumentation